Exceptio Non Adimpleti Contractus Pada Kasus Wanprestasi Dalam Perjanjian Jual Beli - Hasna Farida Brilianto; Devi Siti Hamzah Marpaung (Universitas Widya Gama Malang, 2022)
Contract of sale t is the most commonly used agreement in the business world. The agreement is basically expected to take place fairly, well and proportionally as agreed between the parties. However, in reality, especially for commercial contracts, the fulfillment of contracts is not always smooth, the delays that occur are not only due to delays from one party, but also due to the intentional actions of the other party who have defaulted beforehand. Exceptio non adimpleti contractus is a form of denial of allegations of default. This research is used to find out how to regulate exceptio non adimpleti contractus in Indonesian regulations and what are the legal consequences of implementing exceptio non adimpleti contractus in buying and selling cases. In this study the type of research used is normative juridical research, while the issues discussed, raised and described in this study focus on the application of rules or norms in positive law. Based on the research results, the principle of Exceptio non adimpleti contractus has been regulated in Book III Article 1478 of the Civil Code and Jurisprudence such as the decision of the Supreme Court Number 156 K/SIP/1955. The legal consequence of the application of exceptio non adimpleti contractus is that the claim made by the plaintiff is threatened not to be continued because it is contrary to the principles and rules of the applicable civil procedure so that the lawsuit is not perfect